2019
DOI: 10.1161/circulationaha.119.042891
|View full text |Cite|
|
Sign up to set email alerts
|

A Randomized Trial of a 1-Hour Troponin T Protocol in Suspected Acute Coronary Syndromes

Abstract: Background: High-sensitivity troponin assays promise earlier discrimination of myocardial infarction. Yet, the benefits and harms of this improved discriminatory performance when incorporated within rapid testing protocols, with respect to subsequent testing and clinical events, has not been evaluated in an in-practice patient-level randomized study. This multicenter study evaluated the noninferiority of a 0/1-hour high-sensitivity cardiac troponin T (hs-cTnT) protocol in comparison with a 0/3-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
110
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 36 publications
1
110
3
5
Order By: Relevance
“…One randomised controlled trial of over 3000 participants evaluating the ESCrecommended Roche hs-cTnT assay of 0 and 1 hour, rule-out strategy demonstrated improved clinical effectiveness in terms of rapid discharge from the ED, but compared this strategy to a control group where contemporary cut-offs were used, which may have inflated the results. 23 Our trial has several strengths that distinguish it from prior studies and extend the generalisability of the findings. First, we tested a strategy that does not rely on a risk score.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…One randomised controlled trial of over 3000 participants evaluating the ESCrecommended Roche hs-cTnT assay of 0 and 1 hour, rule-out strategy demonstrated improved clinical effectiveness in terms of rapid discharge from the ED, but compared this strategy to a control group where contemporary cut-offs were used, which may have inflated the results. 23 Our trial has several strengths that distinguish it from prior studies and extend the generalisability of the findings. First, we tested a strategy that does not rely on a risk score.…”
Section: Discussionmentioning
confidence: 68%
“…Third, previous trials have tested hs-cTn assays provided by a single manufacturer. 23 This approach can have significant limitations in terms of generalisability because hospitals may have limited opportunity to change assays. By applying the LoDED strategy across the three different troponin assays in which the undetectable cut-off has been evaluated in observational studies, we have enhanced the generalisability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…These protocols shorten the time of repeat troponin testing from 3-6 hours (Thygesen et al, 2012) to 0-2 hours (Lindahl et al, 2016;McRae et al, 2017). In 2019, a 1-hour protocol was validated in the only randomised trial to date (Chew et al, 2019), which demonstrated non-inferiority to standard-of-care for safety outcomes with reduced emergency department length of stay and subsequent hospital admission (Thygesen et al, 2010). However, these assays come with new challenges including increased identification of troponin elevations above the conventional reference threshold in patients without objective evidence of myocardial ischaemia (Chew et al, 2019;Shah et al, 2018).…”
Section: Myocardial Infarction Myocardial Injury and The Fourth Univmentioning
confidence: 99%
“…Notably, the ESC 0/1 hour algorithm has already been evaluated in a prospective randomised controlled trial. 6 Chew et al randomly assigned 3378 patients with suspected acute coronary syndrome to either the ESC 0/1 hour hs-cTnT pathway, or a standard care arm using hs-cTnT at the 99th centile. They demonstrated an increased rate of discharge from the emergency department with the 0/1 hour algorithm (45.1% vs 32.3%, p<0.001) and a reduced length of stay (4.6, IQR (3.4-6.4) hours vs 5.6 (4.0-7.1) hours, p<0.001).…”
Section: Andrew R Chapman Nicholas L Millsmentioning
confidence: 99%